2020
DOI: 10.1155/2020/9416962
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compound Mixture, Containing Emodin, Genipin, Chlorogenic Acid, Cimigenoside, and Ginsenoside Rb1, Ameliorates Psoriasis‐Like Skin Lesions by Suppressing Inflammation and Proliferation in Keratinocytes

Abstract: Herbal combinations of Rhei Radix et Rhizoma, Gardeniae Fructus, Cimicifugae Rhizoma, and Ginseng Radix have been used in traditional formulas to treat the symptoms of heat and dryness. This study investigated the therapeutic effects of a natural compound mixture (PSM) of these herbal combinations, containing emodin, genipin, chlorogenic acid, cimigenoside, and ginsenoside Rb1, for the treatment of psoriasis and its underlying molecular mechanisms. PSM was applied topically to the dorsal skin lesions of imiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Another compound more present in AP than RP (chlorogenic acid) was also selected, although potentially not active on tyrosinase (See Rf 0.42, Figure 4 ). Indeed, this phenolic acid widely represented in the plant kingdom, has made it possible to expand to other molecular families of the genus Polygonum and was known to be a potential candidate in the treatment of skin diseases [ 76 , 77 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another compound more present in AP than RP (chlorogenic acid) was also selected, although potentially not active on tyrosinase (See Rf 0.42, Figure 4 ). Indeed, this phenolic acid widely represented in the plant kingdom, has made it possible to expand to other molecular families of the genus Polygonum and was known to be a potential candidate in the treatment of skin diseases [ 76 , 77 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Emodin, which is a natural anthraquinone derivative of Dahuang, possesses broad-spectrum pharmacological properties, including antineoplastic, hepatoprotective, antiinflammatory, antioxidant, and antimicrobial functions. The topical application of a natural compound mixture (PSM) of herbs, containing emodin, genipin, chlorogenic acid, cimigenoside, and ginsenoside Rb1, alleviated IMQ-induced psoriasis-like dermatitis and reduced the proliferation rate of IL-22-stimulated keratinocytes (Nguyen et al, 2020b). The therapeutic effects of Dahuang and its chemical compounds in psoriasis requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses a wide range of pharmacological activities, including anticancer, hepatoprotective, anti-inflammatory, antioxidant, and antibacterial effects. In vitro studies confirmed that topical application of a natural compound combination of herbs at a dose 10 μM, which included emodin, lowered the proliferation rate of IL-22-stimulated keratinocytes and relieved IMQ-induced psoriasis-like dermatitis [ 149 ].…”
Section: Substances Of Natural Origin—plants and Phytochemicals With ...mentioning
confidence: 93%